BGA66 and BGA71 facilitate complement resistance of Borrelia bavariensis by inhibiting assembly of the membrane attack complex - Hammerschmidt, Claudia; Klevenhaus, Yvonne; Koenigs, Arno; Hallström, Teresia; Fingerle, Volker; Skerka, Christine; Pos, Klaas Martinus; Zipfel, Peter F.; Wallich, Reinhard; Kraiczy, Peter (Molecular microbiology, 2016)
Borrelia (B.) bavariensis exhibits a marked tropism for nervous tissues and frequently causes neurological manifestations in humans. The molecular mechanism by which B. bavariensis overcomes innate immunity, in particular, complement remains elusive. In contrast to other serum-resistant spirochetes, none of the B. bavariensis isolates investigated bound complement regulators of the alternative (AP) and classical pathway (CP) or proteolytically inactivated complement components. Focusing on outer surface proteins BGA66 and BGA71, we demonstrated that both molecules either inhibit AP, CP and terminal pathway (TP) activation, or block activation of the CP and TP respectively. Both molecules bind complement components C7, C8 and C9, and thereby prevent assembly of the terminal complement complex. This inhibitory activity was confirmed by the introduction of the BGA66 and BGA71 encoding genes into a serum-sensitive B. garinii strain. Transformed spirochetes producing either BGA66 or BGA71 overcome complement-mediated killing, thus indicating that both proteins independently facilitate serum resistance of B. bavariensis. The generation of C-terminally truncated proteins as well as a chimeric BGA71 protein lead to the localization of the complement-interacting binding site within the N-terminus. Collectively, our data reveal a novel immune evasion strategy of B. bavariensis that is directed against the activation of the TP.
Published 05 October 2015
Gesehen am 29.04.2020